2014
DOI: 10.1097/cad.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

3-Bromopyruvate induces apoptosis in breast cancer cells by downregulating Mcl-1 through the PI3K/Akt signaling pathway

Abstract: The hexokinase inhibitor 3-bromopyruvate (3-BrPA) can inhibit glycolysis in tumor cells to reduce ATP production, resulting in apoptosis. However, as 3-BrPA is an alkylating agent, its cytotoxic action may be induced by other molecular mechanisms. The results presented here reveal that 3-BrPA-induced apoptosis is caspase independent. Further, 3-BrPA induces the generation of reactive oxygen species in MDA-MB-231 cells, leading to mitochondria-mediated apoptosis. These results suggest that caspase-independent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…For endometrial cancer, 3-BP induced tumor necrosis in vitro and inhibited tumor growth in vivo [64]. It has also been reported that 3-BP induced apoptosis in MDA-MB-231 breast cancer cells by downregulating Mcl-1 through the PI3K/Akt signaling pathway, which is upstream of HK-II [65]. Recently, Gandham et al also showed that liposomal 3-BP improved permeability, HK-II inhibition, and cytotoxicity in a multicellular spheroid model of human ovarian adenocarcinoma (SKOV-3) cells [66, 67].…”
Section: Agents Targeted Inhibiting the Hk-ii-mediated Warburg Effectmentioning
confidence: 99%
“…For endometrial cancer, 3-BP induced tumor necrosis in vitro and inhibited tumor growth in vivo [64]. It has also been reported that 3-BP induced apoptosis in MDA-MB-231 breast cancer cells by downregulating Mcl-1 through the PI3K/Akt signaling pathway, which is upstream of HK-II [65]. Recently, Gandham et al also showed that liposomal 3-BP improved permeability, HK-II inhibition, and cytotoxicity in a multicellular spheroid model of human ovarian adenocarcinoma (SKOV-3) cells [66, 67].…”
Section: Agents Targeted Inhibiting the Hk-ii-mediated Warburg Effectmentioning
confidence: 99%
“…While mitochondria silencing has long been accepted as general consensus in cancer cells (Warburg effect), recent studies revealed that this intracellular network is still functional, even in cells that shifted cellular energy metabolism to glycolysis [62]. Hence, a potential therapeutic strategy may consist in the re-activation of mitochondrial oxidative metabolism, including by inhibiting glycolysis [63-64]. Interestingly, the glycolytic phenotype of cancer cells has been reported to be induced by Akt upregulation [65].…”
Section: Discussionmentioning
confidence: 99%
“…anti-tumor effect in vivo 18 . The researches of anti-cancer effects of 3BP had a good foundation of papers.…”
Section: Discussionmentioning
confidence: 99%